China under Jiang Zemin - Tien, Hung-mao (Boulder, Colorado : Lynne Rienner, 2000)
Includes bibliographical references and index
Keywords: Chiang, Tze-min, 1926.; China Economic policy 1976.; China Politics and government 1976.; China Social conditions 1976.